Histological Evaluation of the Effect of Concentrated Growth Factor on Bone Healing - BALLI, UMUT; Durmuslar, Mustafa Cenk; Balli, UMUT; Dede, Figen Ongoz; Misir, Ahmet Ferhat; BARIŞ, EMRE; KÜRKÇÜ, MEHMET; Kahraman, Sevil Altindag (My University, 2016)
Objectives:The aim of this study was to evaluate the effects of concentrated growth factors (CGF) on the healing of peri-implant bone defects in an animal model.Study Design:Twenty 4-month-old New Zealand White rabbits, each with an average weight of 3.5kg, were used in this blinded, prospective, experimental study. Two implants were placed and 2 peri-impant defects were prepared in each rabbit tibia. Bone defects were created monocortically in the tibia of each rabbit using a trephine burr with a diameter of 8mm. The implants were installed in each hole. The rabbits were divided into 4 groups: in group E, the defect was left empty; in group CGF, the defects were filled only with CGF; in group AB, the defects were filled with autogenous bone; and in group AB+CGF, the defects were filled with autogenous bone and CGF. The animals were euthanized at week 8 postimplantation. All implants from the 20 animals were fixed in 10% formalin and evaluated histomorphometrically.Results:The mean defect area was highest in group E and lowest in group CGF+AB (P<0.05). The area of the defect differed significantly between groups AB and CGF+AB (P<0.05), but not between groups CGF and E. Implant-to-bone contact was lowest in group E. In the defect areas of groups CGF, AB and CGF+AB, a small amount of new bone formed around the implant.Conclusions:In this animal model of a peri-implant bone defect, restoration was achieved using a combination of autogenous bone and CGF. Further studies are needed to determine the behavior of CGF when used in the repair of bone defects in humans.